Teste de press??o negativa expirat??ria como proposta de screening para a apneia obstrutiva do sono em pacientes com miastenia gravis - Nacif, Sergio Roberto (2014)
Introduction: Obstructive sleep apnea (OSA) is a breathing disorder characterized by the collapse of the upper airway and has significant prevalence in the general population and specifically in neuromuscular diseases. Objective: To determine the effectiveness of the negative expiratory pressure (NEP) test as a screening to the OSA in myasthenia gravis patients. Method: The study included 15 patients (12 women) from the Setor de Investiga????o de Doen??as Neuromusculares and Associa????o Brasileira de Miastenia Grave (ABRAMI), which underwent overnight standard polysomnography (PSG), spirometry, manovacuometer and NEP test. Results: The mean age was 41.46 ?? 11.32 years, mean weight of 78.4 ?? 15.28 kg and the mean body mass index was 29.34 ?? 5,3kg / m2. The physiological variables of sleep observed in PSG draw attention to the oxygen saturation nadir, for the sleep latency and total sleep rapid eyes movement (REM) time, apnea-hypopnea index (AHI) and snoring time. The mean AHI was 17.5 ?? 21.7, being most obstructive origin events. Regarding the Berlin Questionnaire, only one of the fifteen patients evaluated presented low risk for OSA. Regarding the Epworth Sleepiness Scale, we observed that six patients (40%) did not presented excessive daytime sleepiness, three (20%) had mild drowsiness, five individuos presented moderate (33.4%) and only one patient (6.6%) was classified with severe excessive daytime sleepiness with a score of 22 to a maximum of 24 points. The statistics analyses verify the existence of correlation between anthropometric variables, physiological PSG variables, Epworth Sleepiness Scale and Berlin questionnaire show higher values for body mass index (BMI), waist circumference and AHI. Conclusion: We can conclude that patients with MG have lower values of ventilatory maximum pressures associated with normal lung function. They also feature a considerable number of sleep disordered breathing associated with fall oxyhemoglobin saturation and reduced REM sleep, with consequent presence of excessive daytime sleepiness and high risk for OSA. Although we did not observe a correlation between the PNE test with AHI, our data show that patients with moderate-severe OSA have greatly reduced V0,2% (<20%).